2014
DOI: 10.1364/ao.53.001298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of substrate temperatures on the characterization of magnesium fluoride thin films in deep-ultraviolet region

Abstract: As a low refractive index material widely used in coatings for deep-ultraviolet optical systems, magnesium fluoride (MgF2) films were prepared by electron beam evaporation at different substrate temperatures. The effects of the substrate temperatures on the optical properties in vacuum and in air, microstructures, and composition were investigated, as were the microstructures, their composition, and the relation between them. In vacuum, the substrate temperature directly affected the microstructures which domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Similar phenomenon of Al/MgF 2 transmittance filters was reported by Bates and Bradley 13 . This change may be explained by absorption of water in MgF 2 layer 29 and slow continuing oxidation of Al films 13 . When Al is deposited, little oxygen still exists due to gas release from deposition materials although the base pressure of chamber is 1.3 × 10 −4 Pa, and reacts with Al films.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar phenomenon of Al/MgF 2 transmittance filters was reported by Bates and Bradley 13 . This change may be explained by absorption of water in MgF 2 layer 29 and slow continuing oxidation of Al films 13 . When Al is deposited, little oxygen still exists due to gas release from deposition materials although the base pressure of chamber is 1.3 × 10 −4 Pa, and reacts with Al films.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, formed oxide layers undergo gradual structural transformation from amorphous phase to crystalline one 28 . In addition, it is generally accepted that MgF 2 film should be deposited at a high substrate temperature 29 , and Al film should be prepared at room temperature. In order to obtain high reflectance of filters, we do not make the substrate heated.…”
Section: Resultsmentioning
confidence: 99%
“…The F1s peak signal at 684.95 eV suggests its presence in the form of nickel fluoride [31]. However, it is also likely that aluminum fluoride was present as suggested by the broad F1s peak is at 687.75 eV [32][33][34][35]. The presence of aluminum hydroxide [Al(OH) 3 ], nickel hydroxide [Ni(OH) 2 ], and aluminum fluoride (AlF 3 ) cannot be excluded as these are typical by-products of the deposition process which can be incorporated into the coating and seal the pores [23,25,36].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Metal fluorides typically have a low refractive index (1.3–1.6) and a wide band gap (>10 eV), and due to these properties, they are widely used in optical devices. Recently, metal fluorides, AlF 3 and LiF in particular, have also received considerable attention for application in Li-ion batteries, either as a protective layer on the electrodes or as an active electrode material. Furthermore, metal fluorides are of interest as a catalyst for the synthesis of chlorofluorocarbons and hydrofluorocarbons and have been employed in photovoltaics, e.g., as an electron-selective contact. A variety of methods have been used for the deposition of metal fluorides, including evaporation, ,, sputtering, and ion-assisted deposition as well as atomic layer deposition (ALD). Since ALD is a chemical vapor deposition technique that relies on sequential and self-limiting surface reactions, it typically results in highly uniform and conformal ultrathin films. , These characteristics are often relevant for the aforementioned applications of metal fluorides. , ALD of metal fluorides has been reported using various co-reactants, such as NH 4 F, the volatile metal fluorides TaF 5 and TiF 4 , and HF. , Moreover, Lee et al demonstrated the ALD of AlF 3 , ZrF 4 , MnF 2 , HfF 4 , MgF 2 , and ZnF 2 using HF from a HF–pyridine solution. , For the thermal ALD of AlF 3 using HF, it was proposed that the reaction occurs according to the following two reaction equations: In the precursor subcycle (eq ), the Al­(CH 3 ) 3 (trimethylaluminum, TMA) prec...…”
Section: Introductionmentioning
confidence: 99%